115k views
2 votes
Solve - 5x -3 + 4x + 1= -4

User Blackheart
by
4.8k points

2 Answers

2 votes
Answer X = 2 Why because i said so
User Ujjwal Wadhawan
by
5.2k points
1 vote

Answer:

x = 2

Explanation:

Solve for x:

4 x - 5 x - 3 + 1 = -4

Hint: | Group like terms in 4 x - 5 x - 3 + 1.

Grouping like terms, 4 x - 5 x - 3 + 1 = (4 x - 5 x) + (1 - 3):

(4 x - 5 x) + (1 - 3) = -4

Hint: | Combine like terms in 4 x - 5 x.

4 x - 5 x = -x:

-x + (1 - 3) = -4

Hint: | Evaluate 1 - 3.

1 - 3 = -2:

-2 - x = -4

Hint: | Isolate terms with x to the left hand side.

Add 2 to both sides:

(2 - 2) - x = 2 - 4

Hint: | Look for the difference of two identical terms.

2 - 2 = 0:

-x = 2 - 4

Hint: | Evaluate 2 - 4.

2 - 4 = -2:

-x = -2

Hint: | Multiply both sides by a constant to simplify the equation.

Multiply both sides of -x = -2 by -1:

(-x)/(-1) = 2

Hint: | Any nonzero number divided by itself is one.

(-1)/(-1) = 1:

Answer: x = 2

User Memon Irshad
by
4.4k points